Tanshinone IIA Inhibits VEGF Secretion and HIF-1α Expression in Cultured Human Retinal Pigment Epithelial Cells under Hypoxia. (2nd December 2017) - Alzhrani, Rami M.; Alhadidi, Qasim; Bachu, Rinda Devi; Shah, Zahoor; Dey, Surajit; Boddu, Sai HS.
ABSTRACT: Purpose : The current work intends to study the activity of tanshinone IIA on secretion of vascular endothelial growth factor (VEGF) and expression of hypoxia inducible factor 1α (HIF-1α) in human retinal pigment epithelial cells (ARPE-19 cells) under hypoxic condition. Methods : The cytotoxicity of tanshinone IIA was tested in ARPE-19 cells by MTT assay. ARPE-19 cells were incubated with different concentrations of cobalt chloride (100, 150, and 200 µM) for 12 h, and levels of expressed HIF-1α and secreted VEGF were quantified through Western blot and ELISA, respectively. Further, ARPE-19 cells were pretreated for 1 h with different concentrations of tanshinone IIA (5, 10, 15, and 18 µM). After 1 h, the cells were subjected to hypoxic condition using 150 µM cobalt chloride for 12 h in the presence and absence of tanshinone IIA. The cells were then harvested, and the secreted VEGF and expressed HIF-1α was studied. Results : Tanshinone IIA at concentrations of 5, 10, 15, and 18 μM did not show cytotoxicity in ARPE-19 cells. Chemical hypoxia induced by cobalt chloride caused a significant increase in VEGF level in a dose-dependent manner, and HIF-1α expression peaked at 150 µM. Based on the data, cobalt chloride concentration was maintained at 150 μM for further studies. Tanshinone IIA decreased the level of HIF-1α and VEGF secretion in a dose-dependent manner under hypoxic condition. Conclusion : Tanshinone IIA could be explored as a new potential candidate for treating wet AMD.